Factors Affecting Elevated Arsenic and Methyl Mercury Concentrations in Small Shield Lakes Surrounding Gold Mines near the Yellowknife, NT, (Canada) Region - Houben, Adam James; D’Onofrio, Rebecca; Kokelj, Steven V; Blais, Jules M (Université d'Ottawa | University of Ottawa, 2016)
Gold mines in the Yellowknife, NT, region-in particular, the Giant Mine-operated from 1949-99, releasing 237,000 tonnes of waste arsenic trioxide (As2O3) dust, among other compounds, from gold ore extraction and roasting processes. For the first time, we show the geospatial distribution of roaster-derived emissions of several chemical species beyond the mine property on otherwise undisturbed taiga shield lakes within a 25 km radius of the mine, 11 years after its closing. Additionally, we demonstrate that underlying bedrock is not a significant source for the elevated concentrations in overlying surface waters. Aquatic arsenic (As) concentrations are well above guidelines for drinking water (10 μg/L) and protection for aquatic life (5 μg/L), ranging up to 136 μg/L in lakes within 4 km from the mine, to 2.0 μg/L in lakes 24 km away. High conversion ratios of methyl mercury were shown in lakes near the roaster stack as well, with MeHg concentrations reaching 44% of total mercury. The risk of elevated exposures by these metals is significant, as many lakes used for recreation and fishing near the City of Yellowknife are within this radius of elevated As and methyl Hg concentrations.